Perbandingan Sikap Ilmiah Peserta Didik yang menggunakan Model Discovery Learning dan Pembelajaran Langsung (Studi Pada Materi Pokok Larutan Penyangga) - Sugiarti, Sugiarti; Danial, Muhammad; Ratnadillah, Yuli (Universitas Negeri Makassar, 2018)
This study is a comparative study with the quasy experiment method which aims to determine the differences in scientific attitudes of students using the Discovery Learning Model and Direct Learning Models. The research design used was two experimental groups. The data obtained were analyzed using descriptive statistics and inferential statistics. The results of the analysis show the value of the average scientific attitude (curiosity, democratic attitude and academic honesty) of the experimental class I students, namely 74.57 and the experimental class II, which is 64.26. The results of hypothesis testing using the t-test obtained by the value of tcount = 2.30 at a significant level Î± = 0.05 with dk = 5 obtained a value of ttable = 2.021. This shows that there are differences in scientific attitudes of students who are taught through discovery learning models and direct learning models on the subject matter of buffer solutions.